Advancing the 3Rs: innovation, implementation, ethics and society - Grimm, Herwig; Biller-Andorno, Nikola; Buch, Thorsten; Dahlhoff, Maik; Davies, Gail; Cederroth, Christopher R.; Maissen, Otto; Lukas, Wilma; Passini, Elisa; Törnqvist, Elin; Olsson, I. Anna S.; Sandström, Jenny (Frontiers in Veterinary Science, 2023)
The 3Rs principle of replacing, reducing and refining the use of animals in science has been gaining widespread support in the international research community and appears in transnational legislation such as the European Directive 2010/63/EU, a number of national legislative frameworks like in Switzerland and the UK, and other rules and guidance in place in countries around the world. At the same time, progress in technical and biomedical research, along with the changing status of animals in many societies, challenges the view of the 3Rs principle as a sufficient and effective approach to the moral challenges set by animal use in research. Given this growing awareness of our moral responsibilities to animals, the aim of this paper is to address the question: Can the 3Rs, as a policy instrument for science and research, still guide the morally acceptable use of animals for scientific purposes, and if so, how? The fact that the increased availability of alternatives to animal models has not correlated inversely with a decrease in the number of animals used in research has led to public and political calls for more radical action. However, a focus on the simple measure of total animal numbers distracts from the need for a more nuanced understanding of how the 3Rs principle can have a genuine influence as a guiding instrument in research and testing. Hence, we focus on three core dimensions of the 3Rs in contemporary research: (1) What scientific innovations are needed to advance the goals of the 3Rs? (2) What can be done to facilitate the implementation of existing and new 3R methods? (3) Do the 3Rs still offer an adequate ethical framework given the increasing social awareness of animal needs and human moral responsibilities? By answering these questions, we will identify core perspectives in the debate over the advancement of the 3Rs.